Factors That Affect The Financing Volume In The Sharia Commercial Banks - Maya Indriastuti; Indri Kartika (TRIKONOMIKA, 2018)
The aims of this research are to analyze the effect of the Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Third-Party Funds (TPF) to the volume of financing of Sharia Banks in Indonesia. The data used is an annual report from Sharia Commercial Banks in the year of 2014 to 2016, were analyzed by multiple regression analysis. The results of this study indicate that the NPF has a positive insignificant to the volume of financing of Sharia Commercial Banks in Indonesia, FDR and TPF have a positive and significant to the volume of financing of Sharia banks in Indonesia. The implications of this research are for Sharia Commercial Banks to be able to consider the determination of corporate policies and improving operational performance in order to improve the financial performance of the company, especially related to the variables studied and its effects for them.